2003
DOI: 10.1124/jpet.102.042929
|View full text |Cite
|
Sign up to set email alerts
|

(2S,3R)β-Methyl-2′,6′-dimethyltyrosine-l-tetrahydroisoquinoline-3-carboxylic acid [(2S,3R)TMT-l-Tic-OH] Is a Potent, Selective δ-Opioid Receptor Antagonist in Mouse Brain

Abstract: The constrained opioid peptide (2S,3R)␤-methyl-2Ј,6Ј-dimethyltyrosine-L-tetrahydroisoquinoline-3-carboxylic acid [(2S,3R)TMT-LTic-OH] exhibits high affinity and selectivity for the ␦-opioid receptors (Liao et al., 1997). In the present study, we examined the pharmacological properties of (2S,3R)TMT-L-Tic-OH in mouse brain. A 5Ј-O-(3-[ response curve of SNC80 to the right, with a K e value of 3.6 Ϯ 0.7 nM. In contrast, (2S,3R)TMT-L-Tic-OH had no effect on the doseresponse curve of the -selective opioid agonist,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The dipeptide had weak and partial agonist activity in the guinea pig ileum (OPRM1) assay (Table 2). Further extensive studies demonstrated that [2 S ,3 R ]TMT-L-Tic-OH was a potent inverse agonist at the hOPRD1 (44) and a potent and selective OPRD1 neutral antagonist in the mouse brain (45). These comprehensive studies demonstrate several important insights that could be obtained using topographical constraints in addition to those of enhanced potency and receptor selectivity already discussed:

The topographical requirements of the tyrosine pharmacophore moiety for agonist and antagonist activity of opioid peptides at the OPRD1 are similar.

…”
Section: Development Of δ Opioid Receptor Antagonists: Topographical mentioning
confidence: 99%
See 1 more Smart Citation
“…The dipeptide had weak and partial agonist activity in the guinea pig ileum (OPRM1) assay (Table 2). Further extensive studies demonstrated that [2 S ,3 R ]TMT-L-Tic-OH was a potent inverse agonist at the hOPRD1 (44) and a potent and selective OPRD1 neutral antagonist in the mouse brain (45). These comprehensive studies demonstrate several important insights that could be obtained using topographical constraints in addition to those of enhanced potency and receptor selectivity already discussed:

The topographical requirements of the tyrosine pharmacophore moiety for agonist and antagonist activity of opioid peptides at the OPRD1 are similar.

…”
Section: Development Of δ Opioid Receptor Antagonists: Topographical mentioning
confidence: 99%
“… a Data from Reference 43. b Data from Reference 45. Abbreviations: DAMGO, [D-Ala 2 , N -MePhe 4 ,Gly-ol]enkephalin; DPDPE, c[D-Pen 2 ,D-Pen 5 ]enkephalin; GPI, guinea pig ileum; MVD, mouse vas deferens; ND, not determined; TMT, β-methyl-2′,6′-dimethyltyrosine (trimethyltyrosine). …”
Section: Figurementioning
confidence: 99%
“…In this case, both the (2 S ,3 R )-TMT-Tic-OH (IC 50 = 9.3 nM) and the (2 S ,3 S )-TMT-Tic-OH (IC 50 = 124 nM) ligands were found to be potent δ-opioid receptor antagonists in the MVD assay. The most exciting results, however, came when we examined G-protein activation using the GTPγS assay with membranes from δ receptor transfected cell lines and found that the (2 S ,3 R )-TMT-Tic-OH analogue was an inverse agonist at human δ opioid receptor . Inverse agonists are powerful potential drugs when one encounters constituitively active receptors in biological systems…”
Section: A Few Principles In Chemical Biologymentioning
confidence: 99%